Bastiat's 'The Law' - Bastiat, Federic (The Institute of Economic Affairs, 2001)
In Bastiat's 'The Law', Bastiat recognises the central importance of the law and morality in a free society. He was concerned that government was using the 'law' to become too active a participant in the economy whilst devoting too little attention to protecting life and liberty.
Keywords: Non-Fiction; Public policy